2023
DOI: 10.5812/jjcdc-132191
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Anxiety and Caregiver Burden in Informal Caregivers of Patients with COVID-19

Abstract: Background: Irrational health anxiety increases due to insufficient information about COVID-19 and misinterpretation of allergy symptoms in favor of COVID-19. The disease increases the caregiver burden in informal caregivers and, subsequently, causes physical and mental disorders for them and negatively affects the provision of care for patients. Objectives: This study aimed to examine the relationship between health anxiety and caregiver burden in informal caregivers of patients with COVID-19. Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…In the current study, similar to the findings of Arora et al ( 2022 ), Raesi, et al ( 2021 ), Mirzaei et al ( 2020 ), Ebrahimi et al ( 2022 ) and Barghbani et al ( 2023 ), there was no statistically significant association observed between the mean care burden and the age of the caregivers. However, some other studies, such as Jouybari et al ( 2022 ) and Sheikhbardsiri et al ( 2022 ), reported a statistically significant relationship between caregiver age and the care burden.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, similar to the findings of Arora et al ( 2022 ), Raesi, et al ( 2021 ), Mirzaei et al ( 2020 ), Ebrahimi et al ( 2022 ) and Barghbani et al ( 2023 ), there was no statistically significant association observed between the mean care burden and the age of the caregivers. However, some other studies, such as Jouybari et al ( 2022 ) and Sheikhbardsiri et al ( 2022 ), reported a statistically significant relationship between caregiver age and the care burden.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the findings of Ebrahimi et al (2022), the present study revealed that caregivers with poorer health status experienced a higher burden of care when compared to those with better health status. However, the study by Barghbani et al (2023) As the number of patients under care increases, the burden of care also increases. Although no studies specifically examining the relationship between caregiving burden and the number of COVID-19 patients under care were found, it is predicted that an increase in the number of patients will result in an increased caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the IG, we designed a combined intervention using self-determination theory (SDT) and the BRT, which were used separately in previous studies, and successfully reduced the severity of the caregiving burden among caregivers [ 17 , 26 ]. There will be six sessions over six months, where each session will be conducted at the beginning of each month.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques include mindfulness exercises that specifically treat a variety of mental and emotional symptoms such as burden, anxiety, pain, depression, mood swings, and self-esteem. Related studies have demonstrated that BRT is more effective in reducing caregiving burden, anxiety, and depression in various populations, including among caregivers [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%